(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
The relation between design and sustainability presents challenges, as design often drives the continuous production of new products. This article investigates how surface design can contribute to more sustainable practices in textile printing, with a focus on fashion. The gap addressed concerns the lack of clear guidelines to assist designers in creating prints with reduced environmental impact. A qualitative methodology was employed, based on a bibliographic review conducted in the SciELO, CAPES Journal Portal, and Google Scholar databases, in both Portuguese and English, covering the period from 2022 to 2025. Of the 735 studies retrieved, seven met the established inclusion criteria (printing methods, environmental data, and sustainable strategies). The analysis indicated that digital printing with water-based inks, multidirectional patterns, and brick rapport arrangements can reduce textile waste and water consumption by up to 95%, while natural pigments contribute to minimizing effluent toxicity. These strategies underscore the relevance of integrating design decisions with the careful selection of printing techniques to foster sustainability in fashion, in accordance with the principles of the circular economy.